Opposing Effects of Omega-3 and Omega-6 Long Chain Polyunsaturated Fatty Acids on the Expression of Lipogenic Genes in Omental and Retroperitoneal Adipose Depots in the Rat - B. S. Muhlhausler; R. Cook-Johnson; M. James; D. Miljkovic; E. Duthoit; R. Gibson (Journal of Nutrition and Metabolism)
This study aimed to determine the effect of varying dietary intake of the major n-3 PUFA in human diets, α-linolenic acid (ALA; 18 : 3n-3), on expression of lipogenic genes in adipose tissue. Rats were fed diets containing from 0.095%en to 6.3%en ALA and a constant n-6 PUFA level for 3 weeks. Samples from distinct adipose depots (omental and retroperitoneal) were collected and mRNA expression of the pro-lipogenic transcription factors Sterol-Retinoid-Element-Binding-Protein1c (SREBP1c) and Peroxisome Proliferator Activated Receptor-γ (PPARγ), lipogenic enzymes Sterol-coenzyme Desaturase1 (SCD-1), Fatty Acid Synthase (FAS), lipoprotein lipase (LPL) and glycerol-3-phosphate dehydrogenase (G3PDH) and adipokines leptin and adiponectin determined by qRT-PCR. Increasing dietary ALA content resulted in altered expression of SREBP1c, FAS and G3PDH mRNA in both adipose depots. SREBP1c mRNA expression was related directly to n-6 PUFA concentrations (omental, r2=.71; P<.001; Retroperitoneal, r2=.20; P<.002), and inversely to n-3 PUFA concentrations (omental, r2=.59; P<.001; Retroperitoneal, r2=.19; P<.005) independent of diet. The relationship between total n-6 PUFA and SREBP1c mRNA expression persisted when the effects of n-3 PUFA were controlled for. Altering red blood cell concentrations of n-3 PUFA is thus associated with altered expression of lipogenic genes in a depot-specific manner and this effect is modulated by prevailing n-6 PUFA concentrations.